Production of organic plate from napier grass fiber: article - Adnan, Sofiah Hanim; Tan, Huey Ling (2019)
Napier has been studied its potential in replacing plastic as main source of raw material in manufacturing industry for goods. The usage of plastic has been increasing in line with the demands which consequently has negatively affecting our environment. Abundance of plastic waste has led to solid waste management problem and 5.25 trillion plastic floating in our ocean. The objectives of this study were to fabricate organic plate from Napier grass and characterize its chemical, physical and mechanical properties. Soda pulping was applied in this study to soften the grass and produced a pulp. The pulp was then sieved and shaped into plate mold to form a plate. Based on the analysis, SEM images showed there was changes occurred between untreated and treated Napier grass fiber where the treatment managed to give a higher tensile strength to the plate compared to condition before treated. The organic plate has suitable thickness to be used in commercial. Moreover, FTIR analysis proved that soda pulping managed to remove hemicellulose and lignin and left only cellulose to the grass fiber. Drying process removed 85% of moisture content from the organic plate and it has higher resistance to water than oil. Therefore, it is proved that grass can be used as alternative raw material to replace plastic in industry to produce goods.